The Politics of Vocational and Technical Education Curriculum: An Analysis of the Implementation of Vocational and Technical Education in Zimbabwe - Sisimayi, Gideon Wilson; Chikasha, Dr. Adolph Silas (IJRDO- Journal of Educational Research, 2016)
The study sought to analyse pre-colonial era system of vocational and technical education inZimbabwe in contrast with the post-independence period. It defined Curriculum and Politics ineducational issues. The paper looked at the hurdles in the implementation of vocational andtechnical education, citing human interests and attitudes towards vocational and technicaleducation. The study used the interpretivist methodology based on the case study survey design.Open ended in-depth interviews were used to gather data. The study found that there was noreal and clear government policy on vocational and technical education in Zimbabwe’s educationsystem except in theory and on paper. It concluded that it would take decades and decadesbefore true vocationalisation found its way into the country’s education system. The followingwere the main recommendations: Government should appoint a panel of educationists toformulate policy on vocational and technical education in Zimbabwe. Ministry of Finance shouldset aside adequate funds to implement vocational and technical education programmes.